Perceived minerality in sauvignon blanc wine: Chemical reality or cultural construct?. (September 2016) - Parr, Wendy V.; Valentin, Dominique; Breitmeyer, Jason; Peyron, Dominique; Darriet, Philippe; Sherlock, Robert; Robinson, Brett; Grose, Claire; Ballester, Jordi
Abstract: The study aimed to determine the relationship between perceived mineral character in wine and wine chemical composition. We investigated the sensory properties and chemical composition of sauvignon blanc wines from two major sauvignon-producing countries, New Zealand and France. Sensory experiments employing 16 wines (8 French, 8 New Zealand) were conducted in Marlborough, New Zealand and in three regions of France, namely Bordeaux, Burgundy, and the Sancerre/Loire region. Wine professionals (31 New Zealanders and 32 French professionals) sensorially characterised the 16 wines under three conditions, bouquet only (ortho-nasal olfaction), palate only (nose clip condition), and full tasting (global condition: ortho-nasal olfaction, retronasal olfaction, taste, trigeminal stimulation). Sensory data from the global condition only are reported in this article. Physical and chemical analyses conducted on all wines included wine standard parameters, elemental composition, volatile aroma composition, and measures of organic acids. Major results demonstrate that (i) on average French and New Zealand wines were perceived similarly in intensity of mineral character, although judgments to individual wines differed as a function of participant culture; (ii) French and NZ participants drew on different information to make their sensory judgments; and (iii) several aspects of wine composition associated positively with perception of mineral character while others associated negatively, the significant associations differing as a function of participant culture. Graphical abstract: French and New Zealand wine professionals' perceptions of mineral character in sauvignon blanc wine and the association of the sensorial data with wine chemical composition. Highlights: We investigated perceived minerality in sauvignon blanc wine. French and New Zealand tasters judged intensity of mineral character in French and New Zealand wines. Sensory data were associated statistically with wine composition data. Several aspects of wine composition associated positively or negatively with perceived minerality. Free and bound SO2 were the most important wine composition drivers of perceived mineral character.